Forming Foreign Language Communicative Competence of Future Ukrainian Armed Forces Officers by Means of Information and Communication Technologies - Sovhar, Oksana (Educological discourse, 2024)
The article examines strategies employed in foreign language learning which involve employment of Information and Communication Technologies (ICT) in the process of language acquisition in order to create, adapt, and efficiently utilize teaching resources that contribute to the formation of foreign language communicative competence of the future Ukrainian Armed Forces officers. It has been found that the proposed strategies increase the quality of education due to a high level of authenticity and informational relevance, form a stable positive motivation to master the language both in formal and informal settings, contribute to the creation of a situation of success. The findings of the research in introducing ICT in the system of officers language training are based on the experience of teaching the disciplines «Foreign Language» and «Foreign Language for Professional Purposes» during the bachelor’s level of education to cadets of the 27 Automobile Transport Specialty at the Hetman Petro Sahaidachnyi National Army Academy. The sources analysis and the description of the empirical experience of the implementation of ICT tools into the course content are the main research methods employed in the article. The specifics of incorporating ICT in foreign language teaching are outlined in the article, specifying the didactic potential of the aforementioned technologies in increasing the intensity of the learning process, creation of more visual and interesting classes, ensuring instant feedback, enhancing motivation for learners’ cognitive activity, engaging more passive learners, activating learners’ mental abilities, fostering their abstract and logical thinking, and promoting individualization and intensification of learning through independent work with digital resources. Conclusion was made that due to personalization, accessibility, trust, flexibility, productivity, and interactivity, forming and active using of learners’ learning strategies utilizing various ICT in the process of language learning is favourable for acquisition of foreign language competence.